PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN KERAJINAN TEMPURUNG KELAPA DI KELURAHAN KAMASI KECAMATAN TOMOHON TENGAH KOTA TOMOHON - LOMBAN, REAN GEORGINA; TAMPI, GUSTAAF; PLANGITEN, NOVVA (Sam Ratulangi University, 2020)
Coconut shell is a part of coconut fruit in the form of endocrap, which is hard, and covered by coconut fiber, usuallycoconut shell is used as a craft material which is made into something more useful that produces good products thatalso have potential and practical use. Community Empowerment is an effort to increase the capabilities and potentialof the community, so that the community can realize its identity, dignity, and dignity to its full potential to survive anddevelop themselves independently. The purpose of community empowerment is to shape individuals and communitiesto become independent. In the learning process, the community will gradually gain the ability or power from time totime. This study uses descriptive qualitative methods to find out or describe and explain the events under study orresearch conducted on independent variables or variables that is without making comparisons or connecting with othervariables. The results showed that through the craft of coconut shells can have very good benefits for the community ofcraftsmen who can improve their welfare and can produce good products through the capabilities they have and canreduce unemployment and advance the growth of the economic sector of the community. For this reason, thegovernment always supports the coconut shell craftsmen in utilizing the coconut shell.Keywords : Community Empowerment, Crafts, Coconut Shell